Influence of Water Pressure on the Mechanical Properties of Concrete after Freeze-Thaw Attack under Dynamic Triaxial Compression State - Ruijun Wang; Yan Li; Yang Li; Fan Xu; Xiaotong Li; Tenghuan Fu (Advances in Materials Science and Engineering)
This study aims at determining the effect of water pressure on the mechanical properties of concrete subjected to freeze-thaw (F-T) attack under the dynamic triaxial compression state. Two specimens were used: (1) a 100 mm × 100 mm × 400 mm prism for testing the loss of mass and relative dynamic modulus of elasticity (RDME) after F-T cycles and (2) cylinders with a diameter of 100 mm and a height of 200 mm for testing the dynamic mechanical properties of concrete. Strain rates ranged from 10−5·s−1 to 10−3·s−1, and F-T cycles ranged from 0 to 100. Three levels of water pressure (0, 5, and 10 MPa) were applied to concrete. Results showed that as the number of F-T cycles increased, the mass loss rate of the concrete specimen initially decreased and then increased, but the RDME decreased. Under 5 MPa of water pressure and at the same strain rate, the ultimate compressive strength decreased, whereas the peak strain increased with the increase in the number of F-T cycles. This result is contrary to the variation law of ultimate compressive strength and peak strain with the increase in strain rate under the same number of F-T times. With the increase in F-T cycles or water pressure, the strain sensitivity of the dynamic increase factor of ultimate compressive strength and peak strain decreased, respectively. After 100 F-T cycles, the dynamic compressive strength under all water pressure levels tended to increase as the strain rate increased, whereas the peak strain decreased gradually.